Study on Isolated Vertical Ophtalmoplegia and Mydriasis Due to Bilateral Midbrain Infarction - F. Budak; E. Aydin; A. Kockaya; B. Ozkara (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Midbrain infarction rarely causes partial fascicular oculomotor palsy, which is characterised by bilateral midriasis and loss of vertical gaze movements. We describe a patient with acute ischemic infarcts involving both uppermost part of the midbrain, presenting with marked vertical gaze palsy and mydriasis bilaterally as the only neurological abnormality. These features are suggestive of partial fascicular oculomotor palsies involving the pupil, inferior rectus, superior rectus, inferior oblique muscles and sparing medial rectus, levator palpebrae muscles. These neuro-ophthalmological and radiological findings in our case support the model that the fibers to medial rectus and levator palpebrae muscles might be located in the more caudal portion of the oculomotor fascicles.